Greenland, muskoxen on Ymer Island, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig. 119 - Muskoxen on Ymer Island. This photograph was taken on the north side of Dusen Fiord, near its head. August 8, 1931. (VIII). (Caption from Boyd, L.A. (1935). The Fiord Region of East Greenland (pp. 95). New York: American Geographical Society.) Muskoxen on Ymer Island. This photograph was taken on the north side of Dusen Fiord, near the head. August 8, 1931. See: The Fiord Region of East Greenland, Fig. 119. Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society